Multi-instrumented analysis of fatigue behavior and damage mechanisms in jute fiber-reinforced polyester composites. (February 2023) - Alia, Adem; Fantozzi, Gilbert; Godin, Nathalie; Adrien, Jérôme; Osmani, Hocine; Reynaud, Pascal
Highlights: Fatigue damage study of a jute/polyester composite under two plies orientations. Use of several complementary techniques (AE, tomography, stress/strain loops, SEM). Original damage scenarios according to plies orientations and to stress levels. Fatigue due to matrix cracks at low stress, and fiber debonding/breaks at high stress. Major role of yarn cross-links on matrix crack initiation and yarn debonding. Abstract: The present work deals with the fatigue behavior of a jute fiber-reinforced polyester composites. Two stacking sequences were considered [0]8 (JP_0) and [+45/−45]2S (JP_45). The fatigue lifetimes diagrams were determined. They exhibit a fatigue limit lower than 20 MPa for JP_0 composites and lower than 15 MPa for JP_45, whereas the mean ultimate tensile stress σR is 42.9 MPa for JP_0 and 31.1 MPa for JP_45, and the lifetimes lower than 500 000 cycles for JP_0 and 250 000 cycles for JP_45. An exhaustive analysis of the fatigue damage is carried out by combining four approaches: measurement of the mechanical parameters, microscopic observations, X-ray tomography, acoustic emission (AE) monitoring. X-ray tomography revealed the presence of multiple fiber/matrix debondings within transverse yarns for the composites [0]8 and yarn/matrix debondings for the composites [+45/−45]2S . Density of matrix cracks is always more important (about 80%) for JP_45 than for JP_0 at the same relative stress level/σR, and decrease of a 3 times factor for JP_0 (5 for JP_45) when the relative stress increases from 50% to 80%. Two types of behaviors are observed: one for low stresses and another for high stresses. Damage evolution is followed by AE by using a supervised classification with 3 classes of events: matrix cracking, fiber/matrix debonding and fiber breakage. The global activities are at the most of 600 000 signals, and decreases 10 times from 50% σR to 80% σR . The results of AE highlighted in addition the greater number of matrix cracks for low stresses in agreement with X-ray tomography in the same proportions. High stresses are characterized by a larger number of fiber breaks (4 times for both composites) and fibre/matrix debondings (2 times) for JP_0, unless for fiber/matrix debonding in JP_45 which decreases 3 times. The multi-instrumented damage approach allows to make a precise and quantitative analysis of the fatigue damage mechanisms. The results highlight that for the weak stress levels matrix cracking is predominating whereas for the high stress levels the fiber breakages are significant. A scenario of fatigue damage is proposed: for low stresses the behavior is controlled by the matrix and for high stresses the behavior is controlled by the fibers.